The Concepts of Religious Maturity in The Application of Inter-Religious Education Model in Islamic Education - fauziah , Ulfa Nur; Ahmed , Ibrahim Sulaiman; Mufaizin, Mufaizin (Al-Insyiroh: Jurnal Studi Keislaman, 2022)
This study aims to analyze the interreligious education model in Islamic religious education and identify the concept of religious maturity in the application of the interreligious education model in Islamic religious education. This article was written using a qualitative approach and library research. Sources of data are taken from various library sources in the form of journals, books, theses, reports and so on that have relevance to the target object in this study, the researcher then process the data, until finally making the final conclusions from the research results. Overall, the results of the analysis show that the interreligious education model is able to produce characteristics and values in the concept of religious maturity of students, including: 1) tolerance; 2) dynamic; 3) integral; 4) critical; and 5) love. Thus, educators who apply the interreligious education model are actually supporting the process of religious maturity of students. The results of this study are expected to be used as reference material for educators, especially in the subject area of Islamic Religious Education, to be able to dare to open their eyes to the diversity of religions that will be faced by their students in the future, so that efforts are made to apply an interreligious education model which of course remains constant implemented in the corridor of Islamic law.